Implementasi Metode PROMETHEE II Pada Sistem Informasi Geografis (SIG) Dalam Penentuan Lokasi Kafe Terbaik Di Kota Medan - Rifdah Arianto; Ilka Zufria (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
The rapid growth of cafes in Medan City causes difficulties for consumers in choosing the optimal location due to subjective and scattered information. The purpose of the research is to develop a web-based Decision Support System that integrates the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) II method with the Geographic Information System (GIS). The research methodology involved processing spatial and attribute data from 161 cafes using five weighted criteria: distance, atmosphere, facilities, service, and price. PROMETHEE II is used to calculate Net Flow to generate a complete ranking, while GIS visualizes the results on an interactive map. This study successfully identified Monk's Coffee Roasters as the best alternative with a Net Flow of 0.417. Black-box testing shows that all system functionality, including ranking calculations and spatial visualization, is valid. The findings represent the integration of PROMETHEE II and GIS providing an effective and objective tool to facilitate multi-criteria decision-making in the culinary tourism sector, allowing users to filter recommendations based on personal preference and location accessibility.